PENGGUNAAN GAYA BAHASA OLEH PEMBAWA ACARA PADA TAYANGAN PODCAST DEPAN PINTU SERTA RELEVANSI PADA PEMBELAJARAN KEBAHASAAN BAHASA INDONESIA - Wiwit Ramadhani; Astaman, Effiyadi (ADISAM PUBLISHER, 2025)
This research aims to describe the use of the presenter's language style on the Pintu Pintu Podcast broadcast, to describe the relevance of the host's language style on the Tepi Pintu Podcast broadcast on language learning. This research uses a qualitative approach and descriptive research type. Data collection techniques use listening, note-taking and documentation techniques. The data analysis techniques used are documenting, listening, transcribing, identifying, describing and concluding. The results of the research show that the use of the presenter's language style in the Front Door Podcast Show, namely the 12 videos studied. The types of language styles studied in the Doorstep Podcast are comparison and contrast styles of language. Types of comparative language styles include similes, personification and depersonification. The parable contains 1 utterance, personification 3 utterances and depersonification 1 utterance. The conflicting language style contains irony and satire. There is 1 story in irony and 24 stories in satire. The most common satirical style of language. The amount of data found was 30 utterances.The relevance to language learning is that it can be used as Indonesian language teaching material for class IX SMP Semester 1 with KD 3.6, namely examining the structure and linguistic aspects of short stories that are read or heard. This research can be used as reference material in learning Indonesian on short story material for learning language styles because this research examines comparative language styles and conflicting language styles